Human geography of the UK - Dorling, Daniel; Allsopp, Graham; Sage eBooks (London : SAGE, 2005)
Using numerous maps and figures, this text uses different data to describe the social landscape of the United Kingdom. The material covers a range of themes including birth, inequality education, mobility, work and morality, and the book concludes with a comparative analysis of the UK in the global context.
Specialized.
Description based on print version record.
Includes index.
Keywords: Human geography -- Great Britain; Great Britain -- Population; Electronic books